Preußisches Landesbewusstsein in Beglaubigungsmerkmalen öffentlicher Notare des 14. und beginnenden 15. Jahrhunderts - Heckmann, Dieter (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2021)
Prussian national awareness in certification features of public notaries of the 14th and the beginning of the 15th century The signs of Prussian notaries presented in this article fit into the framework of the German type of notary signs, although peculiarities can be recognized that relate to Prussia or to parts of this country. However, examples of this could only be found in small numbers, since the majority of the notarial signs handed down lack any reference to the country. Examples from the years 1417 and 1429 show that public notaries maintained Prussian national awareness even after the great defeat of the Teutonic Order near Tannenberg in 1410.